2004
DOI: 10.1210/en.2003-1699
|View full text |Cite
|
Sign up to set email alerts
|

Androgens Regulate Phosphodiesterase Type 5 Expression and Functional Activity in Corpora Cavernosa

Abstract: By real-time RT-PCR and Western blot analysis, we found that phosphodiesterase type 5 (PDE5) mRNA and protein abundance was several fold higher in human male than in female reproductive tracts. The highest mRNA level (>1 x 10(7) molecules/microg total RNA) was detected in human corpora cavernosa (CC), where PDE5 protein was immunolocalized in both muscular and endothelial compartment. The possible role of androgens in regulating PDE5 expression was studied using a previously established rabbit model of hypogon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
331
2
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(364 citation statements)
references
References 40 publications
25
331
2
6
Order By: Relevance
“…24,25 As T positively controls both the initiation (nitric oxide synthase) and the end (PDE5) of the erectile process, its net effect on erection is modest. Hence, erections are still possible in hypogonadal conditions, in which a decreased cyclic guanosine monophosphate formation, owing to impaired nitric oxide production, is most probably counterbalanced by a reduced PDE5 activity and cyclic guanosine monophosphate hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 As T positively controls both the initiation (nitric oxide synthase) and the end (PDE5) of the erectile process, its net effect on erection is modest. Hence, erections are still possible in hypogonadal conditions, in which a decreased cyclic guanosine monophosphate formation, owing to impaired nitric oxide production, is most probably counterbalanced by a reduced PDE5 activity and cyclic guanosine monophosphate hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…14 IIEF was used to better define the erectile function. The possible scores for the IIEF-5 range from 5 to 25, and ED was classified into five categories based on the scores: severe (5-7), moderate (8)(9)(10)(11), mild to moderate (12)(13)(14)(15)(16), mild (17)(18)(19)(20)(21) and no ED (22)(23)(24)(25). 15 …”
Section: Hrqol Measuresmentioning
confidence: 99%
“…41 Testosterone is a key central and peripheral modulator of erectile function in animal studies. [42][43][44][45] Consistent with these observations, a single-center study of 1050 men seeking new consultation for sexual dysfunction found that 36% had hypogonadism. 46 Buvat and Bou Jaoude, 47 in a compilation of data from 7000 men with ED in 9 large series, reported serum testosterone levels less than 300 ng/dL (to convert to nmol/L, multiply by 0.0347) in 12%, including 4% before and 15% after age 50 years.…”
Section: Recommended Assessments and Risk Clarificationmentioning
confidence: 67%
“…Sildenafil is a well-known inhibitor of PDE5, the major enzymes involved in cyclic guanosine monophosphate (cGMP) breakdown in the penis. 37 Its ability in limiting in a very short time frame BCN-induced penile hypoxia might be related to its effect on PDE5, although other mechanisms of action, independent from PDE5 inhibition, cannot be ruled out. It is interesting to note that similar results on penile oxygenation were previously obtained with a prolonged and continuous exposure to another chemically unrelated PDE5i, tadalafil.…”
Section: Discussionmentioning
confidence: 99%